ROUTLEDGE HANDBOOK OF ESPORTS - Jenny, Seth. ([S.l.] : ROUTLEDGE, 2024)
The Routledge Handbook of Esports offers the first fully comprehensive, interdisciplinary study of esports, one of the fastest growing sectors of the contemporary sports and entertainment industries. Global in coverage, the book emphasizes the multifaceted nature of esports and explores the most pressing issues defining the competitive video gaming landscape today. Featuring the work of 93 leading esports academics and industry specialists from around the world, and rigorously peer-reviewed, the book is structured around ten key themes: 1) Introduction to Esports, 2) Esports Research, 3) Esports Players, 4) Esports Business and Management, 5) Esports Media and Communication, 6) Esports Education, 7) Critical Concerns in Esports, 8) Global Esports Cultures, 9) Esports Future Directions, and 10) Key Terms Definitions. Examining the current state of esports, emerging areas of interest and the ongoing debates shaping the esports industry, each of the 62 chapters offers key highlights, an assessment of the latest research, practical esports examples and recommendations, and is complemented by enlightening case studies or industry interviews. For further academic and professional depth, chapters also include a guide to recommended additional resources. Explaining technical terms and gaming jargon in a user-friendly manner, and maintaining a balanced tone throughout, this handbook is essential reading for any student or researcher with an interest in esports, gaming, or sport studies, and for any practitioner or policy-maker working in the esports industry.
Keywords: eSports (Contests); GAMES / Video & Electronic; SPORTS & RECREATION / Sociology of Sports